Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Answer:
inverse of the function x² - 3x + 7 is [5 ± √(12x - 59)] /6.
Step-by-step explanation:
Let f(x) = y → f-¹y = x → g(y) = x
We need a function g which gives x for g(y).
=> f(x) = y
=> 3x² - 5x + 7 = y
=> x² - x(5/3) + (7/3) = y/3
=> x² - 2x(5/6) + (7/3) = y/3
=> x² - 2x(5/6) + (5/6)² + (7/3) = y/3 + (5/6)²
=> (x - 5/6)² + 7/3 = (y/3 + 25/36)
=> (x - 5/6)² = y/3 + 25/36 - 7/3
=> (x - 5/6)² = (12y + 25 - 84)/36
=> x - 5/6 = ± √(12y - 59) /6
=> x = [ 5 ± √(12y - 59) ]/6
=> x = g(y)
Hence, inverse of the function x² - 3x + 7 is [5 ± √(12x - 59)] /6.
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.